ANALISIS PERAN APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DAN KINERJA PEMERINTAH DESA DALAM MENINGKATKAN KUALITAS ASAS PENGELOLAAN KEUANGAN DESA AKUNTABILITAS SERTA TERTIB DAN DISIPLIN ANGGARAN (Studi Kasus Desa Pandanlandung Kecamatan Wagir Kabupaten Malang) - Annisa Nurul Imani; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2021)
The aim of this study was to analyze the role of thw application of the Village Financial System (Siskeudes) adn the performance of the village government in improving the quality of the principles of village financial management, accountability and budget order and discipline in Pandanlandung Village, Wagir District, Malang Regency. The study was a descriptive qualitative reaserch focusing on aplicatin of the village financial system (Siskeudes) and the performance of the village government. The data were obtained from observation, interviwe and dokumentation. The result of the study showed that the Village Financial System Aplication (Siskeudes) in Pandanlandung Village had an important role in improving the quality of village financial management priciples, especially accountability and budget order and discipline. The permormance of the Village Government has an important role for Pandanlandung Village in improving the quality of the principles of financial management, accountability and budget order and discipline.Keywords: Aplication of financial village system (Siskeudes), Performance of the Village Government, Accountability, budget order an discipling